A kind of quick repair cement mortar and preparation method thereof

Through the synergistic efficiency technology of using active excitants and other components in environmentally friendly quick repair cement mortar, the problem of mechanical properties degradation when increasing the utilization rate of industrial waste slag is solved, and the efficient utilization of industrial waste slag is achieved and the strength of the mortar is improved.

CN118598634BActive Publication Date: 2025-04-11XIYUEFA INT ENVIRONMENTAL PROTECTION NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410665661.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2025-04-11
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

How to ensure the mechanical properties of environmentally friendly quick-repair cement mortar, especially compressive strength and flexural strength while increasing the utilization rate of industrial waste slag.

Method used

By using active activaters, enhancers, thickeners, water reducers, silicate cement and magnesium phosphate cement, the synergistic effect of each component is fully utilized, the hydration activity of fly ash and steel slag powder is stimulated, and the generation of hydration products and structural density are promoted.

Benefits of technology

It significantly improves the utilization rate of industrial waste slag and makes quick repair cement mortar still have high strength under large amounts of fly ash and steel slag powder, meeting the construction needs of the restoration project.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004861002090000101
    Figure BDA0004861002090000101
  • Figure BDA0004861002090000111
    Figure BDA0004861002090000111
Patent Text Reader

Abstract

The present application relates to a quick-repair cement mortar and a preparation method thereof, and relates to the field of environmentally friendly quick-repair cement mortar, which comprises the following components in parts by weight: 30-35 parts of magnesium phosphate cement, 15-20 parts of silicate cement, 37.5-42.5 parts of fly ash, 32.5-37.5 parts of steel slag powder, 90-100 parts of quartz sand, 1-1.5 parts of active activator, 0.25-0.75 parts of reinforcing agent, 0.25-0.3 parts of thickener, 0.25-0.4 parts of water reducer and 66-77 parts of water; the active activator comprises water glass, sodium sulfate, sodium hydroxide and modified polymer dispersant in a weight ratio of (8-10): (5-7): (5-7): (15-20). The present application has the effect of increasing the dosage of industrial waste residue, improving the utilization rate of industrial waste residue and making the quick-repair cement mortar have a higher strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of environmentally friendly quick-repair cement mortar, and in particular to a quick-repair cement mortar and a preparation method thereof. Background Art

[0002] Industrial waste slag refers to toxic, flammable, corrosive, chemically reactive and other harmful solid wastes discharged during industrial production. The long-term storage of industrial waste slag solid waste not only occupies a large amount of land, but also causes serious pollution and harm to the atmospheric system and water resource system. In order to reduce the harm of industrial waste slag to the environment, it is necessary to effectively utilize industrial waste slag. At present, people have developed environmentally friendly quick-repair cement mortar using industrial waste slag as raw materials, which improves the utilization rate of industrial waste slag. In addition, the source of industrial waste slag raw materials is wide, which makes the environmentally friendly quick-repair cement mortar have the advantages of reducing environmental pollution and low preparation cost. Therefore, the environmentally friendly quick-repair cement mortar has broad application prospects.

[0003] Quick-repair cement mortar is used in emergency repair projects of infrastructure such as concrete roads, bridges and airport floors. It has high early strength and excellent durability. With the accelerating pace of life, people have higher requirements for the construction efficiency of repair projects. In order to reduce the impact of repair projects on traffic efficiency, quick-repair cement mortar is required to have a faster hardening speed and higher early strength. Although environmentally friendly quick-repair cement mortar mixed with industrial waste slag has the advantages of low cost and environmental friendliness, as the amount of industrial waste slag increases, the compressive strength and flexural strength of the environmentally friendly quick-repair cement mortar are significantly reduced. Therefore, in order to ensure that the performance of the environmentally friendly quick-repair cement mortar meets the strength requirements of the rapid repair project, it is necessary to limit the amount of industrial waste slag added, resulting in a low utilization rate of industrial waste slag.

[0004] Therefore, how to increase the utilization rate of industrial waste residue while ensuring the mechanical properties of environmentally friendly quick-repair cement mortar has become an urgent problem to be solved in the development process of environmentally friendly quick-repair cement mortar. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a quick-repair cement mortar and a preparation method thereof.

[0006] In the first aspect, the present application provides a quick-repair cement mortar, which adopts the following technical solution:

[0007] A quick-repair cement mortar comprises the following components in parts by weight: 30-35 parts of magnesium phosphate cement, 15-20 parts of silicate cement, 37.5-42.5 parts of fly ash, 32.5-37.5 parts of steel slag powder, 90-100 parts of quartz sand, 1-1.5 parts of an active activator, 0.25-0.75 parts of a reinforcing agent, 0.25-0.3 parts of a thickener, 0.25-0.4 parts of a water reducer and 66-77 parts of water; the active activator comprises water glass, sodium sulfate, sodium hydroxide and a modified polymer dispersant in a weight ratio of (8-10):(5-7):(5-7):(15-20).

[0008] By adopting the above-mentioned technical scheme, the present application fully improves the hydration activity of fly ash and steel slag powder through the synergistic effect between multiple admixtures, promotes the formation of hydration products of fly ash and steel slag powder and makes the structure of the hydration products denser, so that the quick-repair cement mortar with a large amount of industrial waste slag added can still have a higher strength.

[0009] Specifically, the present application uses sodium sulfate and sodium hydroxide to depolymerize the fly ash glass structure, so that the fly ash releases substances with hydration activity, thereby improving the hydration activity of the fly ash, and improves the hydration activity of the steel slag powder through water glass, which is conducive to the generation of more hydration products, and the adhesion performance of water glass can also make the hydration products interweave and bond with each other, so that the structure of the hydration products is more compact, which is conducive to improving the strength of the quick-repair cement mortar. At the same time, the present application adopts a modified polymer dispersant and water glass and other components for mixed use, and uses the modified polymer dispersant to improve the dispersibility of each component in the quick-repair cement mortar, thereby improving the stimulating effect of water glass, sodium sulfate and sodium hydroxide in the active stimulator on fly ash and steel slag powder, so that the fly ash and steel slag powder have higher hydration activity, thereby improving the strength of the quick-repair cement mortar.

[0010] The present application also adds a reinforcing agent to the quick-repair cement mortar, and utilizes the reinforcing agent to further increase the hydration rate of fly ash and steel slag powder, thereby increasing the amount of hydration products of fly ash and steel slag powder, and further increasing the strength of the quick-repair cement mortar.

[0011] At the same time, the present application compounded magnesium phosphate cement and silicate cement. The hydration product or unhydrated clinker particles of silicate cement can react with the phosphate in the magnesium phosphate cement to generate phosphate-calcium products with gel properties, which is beneficial to increase the amount of hydration products, thereby improving the strength of the quick-repair cement mortar. The hydration product of silicate cement, calcium hydroxide, can be used as an alkali activator, further improving the hydration activity of fly ash and steel slag powder, increasing the amount of hydration products generated, and improving the improvement effect of fly ash and steel slag powder on the fluidity of the quick-repair cement mortar. The water-cement ratio is further reduced by compounding with a water reducer and a thickener, thereby further improving the strength of the quick-repair cement mortar.

[0012] In summary, the present application adopts a mixture of active stimulants, enhancers, thickeners, water reducers, silicate cement and magnesium phosphate cement, giving full play to the synergistic effect of each component, greatly stimulating the hydration activity of fly ash and steel slag powder, and promoting fly ash and steel slag powder to generate more densely structured hydration products, so that the quick repair cement mortar still has high strength under the condition of large amounts of fly ash and steel slag powder. The total proportion of fly ash and steel slag powder in the quick repair cement mortar of the present application in the cementitious material is 56%-64%, which is 21%-33% higher than the utilization rate of industrial waste slag of other environmentally friendly quick repair cement mortars. The present application significantly improves the utilization rate of industrial waste slag and makes the quick repair cement mortar have a higher strength to meet the construction needs of the repair project.

[0013] Preferably, the modified polymer dispersant is prepared by the following method:

[0014] Sodium styrene sulfonate, N,N-dimethylacrylamide, a chain initiator and a chain transfer agent in a molar ratio of (16-22):(3-6):(0.1-0.2):(0.1-0.2) are dissolved in a solvent, and then heated to 75-85°C under the protection of an inert gas while stirring, react for 4-5 hours, and then distill under reduced pressure for 1.5-2 hours to obtain a modified polymer dispersant.

[0015] By adopting the above technical scheme, the modified polymer dispersant generated by the free radical polymerization reaction of sodium styrene sulfonate and N,N-dimethylacrylamide has good dispersing properties, and at the same time has good adhesion and thickening effects. While improving the stimulating effect of water glass, sodium sulfate and sodium hydroxide in the active activator on fly ash and steel slag powder, it also improves the adhesion between hydration products, and plays a synergistic role with thickeners and water reducers, making the structure of hydration products more compact, thereby improving the strength of quick-repair cement mortar. In addition, the modified polymer dispersant also has a certain corrosion inhibition effect, which reduces the influence of hydroxide ions and sulfate ions in the active activator on the stability of quick-repair cement mortar, thereby improving the stability and later strength of quick-repair cement mortar.

[0016] Preferably, the enhancer comprises nanoparticles, triethanolamine and ethylenediaminetetraacetic acid in a weight ratio of (3-5):(2-4):(1-3).

[0017] By adopting the above technical scheme, triethanolamine, ethylenediaminetetraacetic acid and nanoparticles synergistically promote the hydration process of fly ash and steel slag powder in quick-repair cement mortar, improve the stability of steel slag powder, reduce the late shrinkage of quick-repair cement mortar, and thus improve the strength of quick-repair cement mortar. Among them, triethanolamine promotes the hydration process of fly ash and steel slag powder by promoting the dissolution of metal ions in fly ash and steel slag powder. At the same time, ethylenediaminetetraacetic acid consumes free calcium oxide and low-activity components in steel slag by promoting carbonization, thereby improving the stability of steel slag powder, thereby improving the strength of quick-repair cement mortar. In addition, triethanolamine accelerates the hydration rate of C3A, and nanoparticles increase the hydration rate of C3S through nucleation. The synergistic effect of the two increases the hydration rate of silicate cement, which is conducive to the quick-repair cement mortar having higher strength.

[0018] Preferably, the nanoparticles include nano-silicon dioxide and nano-titanium nitride in a weight ratio of (5-7):(3-6).

[0019] By adopting the above technical scheme, nano-silicon dioxide and nano-titanium nitride can fill the gaps between hydration products while playing the role of crystal nuclei to promote the hydration process, making the hydration products denser. This application fully utilizes the synergistic effect of nano-silicon dioxide and nano-titanium nitride to further improve the strength of quick-repair cement mortar.

[0020] Preferably, the particle size of the fly ash is 10-20 μm, and the particle size of the steel slag powder is 15-25 μm.

[0021] By adopting the above-mentioned technical scheme, the particle size range of fly ash and steel slag powder provided in the present application optimizes the particle size grading of fly ash and steel slag powder, so that both fly ash and steel slag powder have high hydration activity and dispersibility, and at the same time makes the structure of the quick-repair cement mortar dense, thereby improving the strength of the quick-repair cement mortar.

[0022] Preferably, the quartz sand comprises 20-40 mesh quartz sand, 40-80 mesh quartz sand and 80-120 mesh quartz sand in a weight ratio of (1-3):(3-7):(6-10).

[0023] By adopting the above technical solution, the present application adopts quartz sand of different grades and optimizes the ratio, so that the structure of the quick-repair cement mortar is dense, thereby making the quick-repair cement mortar have higher strength.

[0024] Preferably, the thickener is hydroxypropyl methylcellulose ether.

[0025] By adopting the above technical scheme, hydroxypropyl methylcellulose ether has the functions of water retention, thickening and air entraining. Hydroxypropyl methylcellulose ether improves the fluidity and adhesion of the quick-repair cement mortar, and the small amount of gas introduced provides space for the later hydration products of steel slag powder and fly ash, reducing the expansion and cracking of the quick-repair cement mortar, thereby improving the stability and strength of the quick-repair cement mortar.

[0026] In a second aspect, the present application provides a method for preparing a quick-repair cement mortar, comprising the following steps:

[0027] The magnesium phosphate cement, silicate cement, fly ash, steel slag powder, quartz sand, active activator, reinforcing agent, thickener, water reducing agent and water are uniformly mixed according to weight to prepare the quick repair cement mortar.

[0028] In summary, this application has the following beneficial technical effects:

[0029] 1. The present application activates and enhances fly ash and steel slag powder through active activators and enhancers, promotes the generation of their hydration products and improves the density of the hydration products, so that the quick-repair cement mortar still has a high strength when a large amount of industrial waste slag is added;

[0030] 2. The present application further promotes the formation of densely structured hydration products by compounding magnesium phosphate cement and silicate cement, and synergistically reduces the water-cement ratio with thickeners and water reducers, thereby further improving the strength of the quick-repair cement mortar;

[0031] 3. This application further improves the density of the quick-repair cement mortar by optimizing the particle size gradation of fly ash, steel slag powder and quartz sand, thereby further improving the strength of the quick-repair cement mortar. DETAILED DESCRIPTION

[0032] Material Source

[0033] Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically:

[0034] Magnesium phosphate cement was purchased from Guizhou Phosphorus Magnesium Materials Co., Ltd., item number 001, strength grade M60, magnesium oxide content 60%-70%, cement fineness 100-200 mesh;

[0035] The silicate cement was purchased from Dongsheng Building Materials Business Department in Shawan District, Leshan City. The model is 52.5 grade ordinary silicate cement with a strength grade of 52.5R.

[0036] The fly ash was of grade I, purchased from Shijiazhuang Daheng Mineral Products Processing Co., Ltd., including fly ash with particle sizes of 5-10 μm, 10-20 μm, and 20-40 μm;

[0037] Steel slag powder was purchased from Henan Jinhan Environmental Protection Technology Co., Ltd., item number 004, including steel slag powder with particle sizes of 10-15 μm, 15-25 μm, and 35-45 μm;

[0038] Quartz sand was purchased from Lingshou County Dechang Mineral Products Processing Plant, including quartz sand with a particle size of 20-40 mesh, quartz sand with a particle size of 40-80 mesh, and quartz sand with a particle size of 80-120 mesh;

[0039] Water glass was purchased from Xi'an Huachang Water Glass Co., Ltd., CAS No. 6834-92-0, active ingredient content of 99%, industrial grade;

[0040] Sodium sulfate was purchased from Weifang Ruicheng Chemical Co., Ltd., with a CAS number of 7757-82-6, an active ingredient content of 99%, and a high-quality grade;

[0041] The cement mortar enhancer was purchased from Guangzhou Jiabaili Waterproof Engineering Co., Ltd., model number is JBL-12;

[0042] Sodium hydroxide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Sodium styrene sulfonate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0044] N,N-Dimethylacrylamide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0045] Azobisisobutylimidazoline hydrochloride was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0046] 3-Mercaptopropionic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0047] Nano-titanium dioxide was purchased from Ningbo Jiwei Nano New Material Technology Co., Ltd., model JWN-TO-R30, with an average particle size of 30 nm;

[0048] Nano-titanium nitride was purchased from Ningbo Denai Nano Coating Co., Ltd., model DK-TIN-001, with an average particle size of 20 nm;

[0049] Nano calcium carbonate was purchased from Shanghai Liangjiang Titanium Dioxide Chemical Co., Ltd., model LP600, with an average particle size of 15-40 nm;

[0050] Triethanolamine was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0051] Ethylenediaminetetraacetic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0052] Hydroxypropyl methylcellulose ether was purchased from Wuhan Runxingyuan Co., Ltd.;

[0053] Sodium gluconate was purchased from Shandong Junda Chemical Co., Ltd.;

[0054] Sodium dodecyl sulfate was purchased from Henan Binhua Chemical Co., Ltd.;

[0055] The polycarboxylate water reducer was purchased from Shanxi Bajunma Building Materials Co., Ltd., and its model number is D0001;

[0056] The chain initiator used in the preparation example of the present application is azobisisobutylimidazoline hydrochloride, the chain transfer agent is 3-mercaptopropionic acid, and the solvent used is deionized water.

[0057] Preparation Example 1

[0058] The preparation method of the modified polymer dispersant comprises the following steps:

[0059] 1649.6 g of sodium styrene sulfonate, 213.3 g of N,N-dimethylacrylamide, 13.19 g of azobisisobutylimidazoline hydrochloride and 7.9 g of 3-mercaptopropionic acid were dissolved in 13750 mL of deionized water to prepare a reaction solution, which was added to a reaction vessel equipped with a stirrer and a condenser, and nitrogen was introduced into the reaction vessel to exhaust oxygen in the reaction system, and then the reaction solution was stirred and heated to 75° C. and reacted for 5 hours. Finally, the reaction solution was subjected to reduced pressure distillation for 1.5 hours to remove deionized water to obtain a modified polymer dispersant.

[0060] Preparation Example 2

[0061] The preparation method of the modified polymer dispersant comprises the following steps:

[0062] 2268.2g of sodium styrene sulfonate, 106.7g of N,N-dimethylacrylamide, 26.38g of azobisisobutylimidazoline hydrochloride and 4.0g of 3-mercaptopropionic acid were dissolved in 10410mL of deionized water to prepare a reaction solution, and the reaction solution was added to a reaction vessel equipped with a stirrer and a condenser, and nitrogen was introduced into the reaction vessel to exhaust oxygen in the reaction system, and then the reaction solution was stirred and heated to 85°C, reacted for 4h, and finally the reaction solution was subjected to reduced pressure distillation for 2h to remove deionized water to obtain a modified polymer dispersant.

[0063] Preparation Example 3

[0064] The preparation method of the modified polymer dispersant comprises the following steps:

[0065] 1443.4 g of sodium styrene sulfonate, 2844 g of N,N-dimethylacrylamide, 10.63 g of azobisisobutylimidazoline hydrochloride and 9.5 g of 3-mercaptopropionic acid were dissolved in 13750 mL of deionized water to prepare a reaction solution, which was added to a reaction vessel equipped with a stirrer and a condenser, and nitrogen was introduced into the reaction vessel to exhaust oxygen in the reaction system, and then the reaction solution was stirred and heated to 75° C. and reacted for 5 hours. Finally, the reaction solution was subjected to reduced pressure distillation for 1.5 hours to remove deionized water to obtain a modified polymer dispersant.

[0066] Preparation Example 4

[0067] The preparation method of the modified polymer dispersant comprises the following steps:

[0068] 2680.6g of sodium styrene sulfonate, 71.1g of N,N-dimethylacrylamide, 31.7g of azobisisobutylimidazoline hydrochloride and 3.2g of 3-mercaptopropionic acid were dissolved in 17500mL of deionized water to prepare a reaction solution, and the reaction solution was added to a reaction vessel equipped with a stirrer and a condenser, and nitrogen was introduced into the reaction vessel to exhaust oxygen in the reaction system, and then the reaction solution was stirred and heated to 75°C, reacted for 5h, and finally the reaction solution was subjected to reduced pressure distillation for 1.5h to remove deionized water to obtain a modified polymer dispersant.

[0069] Preparation Example 5

[0070] The difference from Preparation Example 1 is that the reaction solution was heated to 65°C.

[0071] Preparation Example 6

[0072] The difference from Preparation Example 1 is that the reaction solution is heated to 95°C.

[0073] Example 1

[0074] A method for preparing quick-repair cement mortar comprises the following steps:

[0075] 30 kg of magnesium phosphate cement, 20 kg of silicate cement, 37.5 kg of fly ash, 37.5 kg of steel slag powder, 90 kg of quartz sand, 1.5 kg of active activator, 0.25 kg of reinforcing agent, 0.3 kg of hydroxypropyl methylcellulose ether, 0.25 kg of polycarboxylic acid type water reducer and 77 kg of water were uniformly mixed to prepare quick repair cement mortar.

[0076] Among them, the active activator includes 0.3kg water glass, 0.2625kg sodium sulfate, 0.1875kg sodium hydroxide and 0.75kg modified polymer dispersant, the reinforcing agent includes 0.0426kg nano silicon dioxide, 0.0511kg nano titanium nitride, 0.125kg triethanolamine and 0.0313kg ethylenediaminetetraacetic acid, and the quartz sand includes 6.429kg quartz sand with a particle size of 20-40 mesh, 45kg quartz sand with a particle size of 40-80 mesh and 38.571kg quartz sand with a particle size of 80-120 mesh. The modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 1, the particle size of the fly ash used is 10-20μm, and the particle size of the steel slag powder used is 15-25μm.

[0077] Example 2

[0078] A method for preparing quick-repair cement mortar comprises the following steps:

[0079] 35 kg of magnesium phosphate cement, 15 kg of silicate cement, 42.5 kg of fly ash, 32.5 kg of steel slag powder, 100 kg of quartz sand, 1 kg of active activator, 0.75 kg of reinforcing agent, 0.25 kg of hydroxypropyl methylcellulose ether, 0.4 kg of polycarboxylic acid type water reducing agent and 66 kg of water were uniformly mixed to prepare quick repair cement mortar.

[0080] Among them, the active activator includes 0.2kg water glass, 0.175kg sodium sulfate, 0.125kg sodium hydroxide and 0.5kg modified polymer dispersant, the reinforcing agent includes 0.1278kg nano silicon dioxide, 0.1534kg nano titanium nitride, 0.375kg triethanolamine and 0.0938kg ethylenediaminetetraacetic acid, and the quartz sand includes 7.143kg quartz sand with a particle size of 20-40 mesh, 50kg quartz sand with a particle size of 40-80 mesh and 42.857kg quartz sand with a particle size of 80-120 mesh. The modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 1, the particle size of the fly ash used is 10-20μm, and the particle size of the steel slag powder used is 15-25μm.

[0081] Example 3

[0082] The difference from Example 1 is that the active activator contains 0.4054 kg of water glass, 0.2027 kg of sodium sulfate, 0.2838 kg of sodium hydroxide, and 0.6081 kg of modified polymer dispersant.

[0083] Example 4

[0084] The difference from Example 1 is that the reinforcing agent includes 0.0568 kg of nano silicon dioxide, 0.0681 kg of nano titanium nitride, 0.05 kg of triethanolamine and 0.075 kg of ethylenediaminetetraacetic acid.

[0085] Example 5

[0086] The difference from Example 1 is that the reinforcing agent contains 0.0656 kg of nano silicon dioxide and 0.0281 kg of nano titanium nitride.

[0087] Example 6

[0088] The difference from Example 1 is that the quartz sand includes 16.875 kg of quartz sand with a particle size of 20-40 mesh, 16.875 kg of quartz sand with a particle size of 40-80 mesh, and 56.25 kg of quartz sand with a particle size of 80-120 mesh.

[0089] Example 7

[0090] The difference from Example 1 is that the modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 2.

[0091] Example 8

[0092] The difference from Example 1 is that the modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 3.

[0093] Example 9

[0094] The difference from Example 1 is that the modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 4.

[0095] Example 10

[0096] The difference from Example 1 is that the modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 5.

[0097] Embodiment 11

[0098] The difference from Example 1 is that the modified polymer dispersant used is the modified polymer dispersant prepared in Preparation Example 6.

[0099] Example 12

[0100] The difference from Example 1 is that the enhancer includes 0.2 kg triethanolamine and 0.05 kg ethylenediaminetetraacetic acid.

[0101] Embodiment 13

[0102] The difference from Example 1 is that the reinforcing agent includes 0.0852 kg of nano silicon dioxide, 0.1023 kg of nano titanium nitride and 0.05 kg of ethylenediaminetetraacetic acid.

[0103] Embodiment 14

[0104] The difference from Example 1 is that the reinforcing agent includes 0.0487 kg of nano silicon dioxide, 0.0584 kg of nano titanium nitride and 0.1429 kg of triethanolamine.

[0105] Embodiment 15

[0106] The difference from Example 1 is that the reinforcing agent includes 0.0938 kg of nano-silicon dioxide, 0.125 kg of triethanolamine and 0.0313 kg of ethylenediaminetetraacetic acid.

[0107] Example 16

[0108] The difference from Example 1 is that the reinforcing agent includes 0.0938 kg of nano titanium nitride, 0.125 kg of triethanolamine and 0.0313 kg of ethylenediaminetetraacetic acid.

[0109] Embodiment 17

[0110] The difference from Example 1 is that nano silicon dioxide is replaced by nano calcium carbonate.

[0111] Embodiment 18

[0112] The difference from Example 1 is that nano-titanium nitride is replaced by nano-calcium carbonate.

[0113] Embodiment 19

[0114] The difference from Example 1 is that the reinforcing agent is replaced by a cement mortar reinforcing agent with model number JBL-12.

[0115] Embodiment 20

[0116] The difference from Example 1 is that the reinforcing agent includes 0.0284 kg of nano silicon dioxide, 0.0341 kg of nano titanium nitride, 0.1563 kg of triethanolamine and 0.0313 kg of ethylenediaminetetraacetic acid.

[0117] Embodiment 21

[0118] The difference from Example 1 is that the reinforcing agent includes 0.0757 kg of nano silicon dioxide, 0.0909 kg of nano titanium nitride, 0.0278 kg of triethanolamine and 0.0556 kg of ethylenediaminetetraacetic acid.

[0119] Embodiment 22

[0120] The difference from Example 1 is that the reinforcing agent contains 0.0313 kg of nano silicon dioxide and 0.0625 kg of nano titanium nitride.

[0121] Embodiment 23

[0122] The difference from Example 1 is that the reinforcing agent contains 0.0767 kg of nano silicon dioxide and 0.017 kg of nano titanium nitride.

[0123] Embodiment 24

[0124] The difference from Example 1 is that the particle size of the fly ash used is 20-40 μm.

[0125] Embodiment 25

[0126] The difference from Example 1 is that the particle size of the fly ash used is 5-10 μm.

[0127] Embodiment 26

[0128] The difference from Example 1 is that the particle size of the steel slag powder used is 35-45 μm.

[0129] Embodiment 27

[0130] The difference from Example 1 is that the particle size of the fly ash used is 10-15 μm.

[0131] Embodiment 28

[0132] The difference from Example 1 is that the modified polymer dispersant prepared in Preparation Example 1 is replaced by sodium styrene sulfonate.

[0133] Embodiment 29

[0134] The difference from Example 1 is that the modified polymer dispersant prepared in Preparation Example 1 is replaced by N,N-dimethylacrylamide.

[0135] Embodiment 30

[0136] The difference from Example 1 is that hydroxypropyl methylcellulose ether is replaced by sodium gluconate.

[0137] Embodiment 31

[0138] The difference from Example 1 is that hydroxypropyl methylcellulose ether is replaced by sodium dodecyl sulfate.

[0139] Comparative Example 1

[0140] The difference from Example 1 is that no active stimulant is contained.

[0141] Comparative Example 2

[0142] The difference from Example 1 is that no reinforcing agent is contained.

[0143] Comparative Example 3

[0144] The difference from Example 1 is that hydroxypropyl methylcellulose ether is not contained.

[0145] Comparative Example 4

[0146] The difference from Example 1 is that the active stimulant includes 0.6 kg of water glass, 0.525 kg of sodium sulfate and 0.375 kg of sodium hydroxide.

[0147] Comparative Example 5

[0148] The difference from Example 1 is that the active activator contains 0.2195 kg of water glass, 0.3292 kg of sodium sulfate, 0.1463 kg of sodium hydroxide, and 0.8049 kg of modified polymer dispersant.

[0149] Comparative Example 6

[0150] The difference from Example 1 is that the active activator contains 0.4865 kg of water glass, 0.1622 kg of sodium sulfate, 0.3648 kg of sodium hydroxide, and 0.4865 kg of modified polymer dispersant.

[0151] Comparative Example 7

[0152] The difference from Example 1 is that silicate cement is replaced by magnesium phosphate cement.

[0153] Comparative Example 8

[0154] The difference from Example 1 is that magnesium phosphate cement is replaced by silicate cement.

[0155] Performance Testing

[0156] According to GB / T 17671-1999 “Test method for strength of cement mortar”, the compressive strength and flexural strength of Examples 1-31 and Comparative Examples 1-8 were tested. The test results are shown in Table 1.

[0157] Table 1 Test results of compressive strength and flexural strength of quick-repair cement mortar

[0158]

[0159]

[0160]

[0161] It can be seen from Table 1 that the 3d compressive strength of Examples 1-2 of the present application are 35.32 MPa and 35.61 MPa respectively, the 28d compressive strength are 66.75 MPa and 67.11 MPa respectively, the 3d flexural strength are 5.32 MPa and 5.49 MPa respectively, and the 28d flexural strength are 9.87 MPa and 10.12 MPa respectively, indicating that the components and proportions of the quick-repair cement mortar provided in the present application make the quick-repair cement mortar have higher compressive strength and flexural strength.

[0162] The various performance indicators of Example 3 of the present application are close to those of Example 1, indicating that the ratio range of the active stimulant provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0163] The various performance indicators of Example 4 of the present application are close to those of Example 1, indicating that the ratio range of the reinforcing agent provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0164] The various performance indicators of Example 5 of the present application are close to those of Example 1, indicating that the ratio range of the nanoparticles provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0165] The various performance indicators of Example 6 of the present application are close to those of Example 1, indicating that the ratio range of quartz sand of different particle sizes provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0166] The various performance indicators of Example 7 of the present application are close to those of Example 1, indicating that the ratio range of the modified polymer dispersant provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0167] Compared with Example 1, the 3d and 28d compressive strengths of Example 8 of the present application are reduced by 1.59 MPa and 2.21 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.61 MPa and 1.44 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 9 of the present application are reduced by 1.9 MPa and 2.48 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.96 MPa and 1.7 MPa, respectively, indicating that the ratio range of the modified polymer dispersant provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0168] Compared with Example 1, the 3d and 28d compressive strengths of Example 10 of the present application are reduced by 1.64 MPa and 2.37 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.7 MPa and 1.61 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 11 of the present application are reduced by 1.98 MPa and 2.57 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 1.09 MPa and 1.81 MPa, respectively, indicating that the preparation temperature range of the modified polymer dispersant provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0169] Compared with Example 1, the 3d and 28d compressive strengths of Example 12 of the present application are reduced by 3.73 MPa and 6.63 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 1.71 MPa and 2.04 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 13 of the present application are reduced by 3.41 MPa and 6.02 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 1.56 MPa and 1.98 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 14 of the present application are reduced by 3.15 MPa and 3.78 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 1.4 MPa and 1.96 MPa, respectively, indicating that there is a good synergistic effect between the components of the enhancer provided in the present application, which has a good effect on improving the strength of the quick-repair cement mortar.

[0170] Compared with the 3d and 28d compressive strength in Example 1, Example 15 of the present application is reduced by 3.11MPa and 3.64MPa, respectively, and the 3d and 28d flexural strength is reduced by 1.29MPa and 1.89MPa, respectively. Compared with the 3d and 28d compressive strength in Example 16 of the present application is reduced by 3.25MPa and 3.91MPa, respectively, and the 3d and 28d flexural strength is reduced by 1.46MPa and 2.05MPa, respectively. Compared with the 3d and 28d compressive strength in Example 1, Example 17 of the present application is reduced by 1. The strength was reduced by 2.08MPa and 2.63MPa respectively, and the 3d and 28d flexural strength was reduced by 1.15MPa and 1.83MPa respectively. Compared with Example 1, the 3d and 28d compressive strength of Example 18 of the present application was reduced by 2.16MPa and 2.72MPa respectively, and the 3d and 28d flexural strength was reduced by 1.23MPa and 1.86MPa respectively, indicating that there is a good synergistic effect between the two nanoparticles provided in the present application, which has a good effect on improving the strength of quick-repair cement mortar.

[0171] Compared with Example 1, the 3d and 28d compressive strengths of Example 19 of the present application are reduced by 4.56 MPa and 8.11 MPa respectively, and the 3d and 28d flexural strengths are reduced by 1.5 MPa and 2.45 MPa respectively, indicating that the reinforcing agent provided in the present application has a good effect on improving the strength of quick-repair cement mortar.

[0172] Compared with Example 1, the 3d and 28d compressive strengths of Example 20 of the present application are reduced by 1.87 MPa and 2.11 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.91 MPa and 1.64 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 21 of the present application are reduced by 1.79 MPa and 1.99 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.8 MPa and 1.54 MPa, respectively, indicating that the ratio range of the enhancer provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0173] Compared with Example 1, the 3d and 28d compressive strengths of Example 22 of the present application are reduced by 1.29 MPa and 1.43 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.44 MPa and 1.23 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 23 of the present application are reduced by 1.4 MPa and 1.78 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.57 MPa and 1.34 MPa, respectively, indicating that the ratio range of nanoparticles provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0174] Compared with Example 1, the compressive strength of 3d and 28d in Example 24 of the present application is reduced by 5.55 MPa and 9.86 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1.85 MPa and 2.78 MPa, respectively. Compared with Example 1, the compressive strength of 3d and 28d in Example 25 of the present application is reduced by 3.13 MPa and 3.77 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1.37 MPa and 1.94 MPa, respectively. This shows that the fly ash with a particle size of 10-20 μm provided in the present application has higher hydration activity than the fly ash with a particle size of 20-40 μm, and has lower surface energy and higher dispersibility than the fly ash with a particle size of 5-10 μm. Therefore, the fly ash with a particle size of 10-20 μm provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0175] Compared with Example 1, the compressive strength of 3d and 28d in Example 26 of the present application is reduced by 5.95 MPa and 10.13 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1.93 MPa and 2.94 MPa, respectively. Compared with Example 1, the compressive strength of 3d and 28d in Example 27 of the present application is reduced by 2.8 MPa and 3.99 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1 MPa and 1.71 MPa, respectively. This shows that the steel slag powder with a particle size of 15-25 μm provided in the present application has higher hydration activity than the steel slag powder with a particle size of 35-45 μm, and has lower surface energy and higher dispersibility than the steel slag powder with a particle size of 10-15 μm. Therefore, the steel slag powder with a particle size of 15-25 μm provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0176] Compared with Example 1, the compressive strength of 3d and 28d in Example 28 of the present application is reduced by 3.67 MPa and 6.38 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1.65 MPa and 1.96 MPa, respectively. Compared with Example 1, the compressive strength of 3d and 28d in Example 29 of the present application is reduced by 3.85 MPa and 6.67 MPa, respectively, and the flexural strength of 3d and 28d is reduced by 1.68 MPa and 2.11 MPa, respectively, indicating that the modified polymer dispersant provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0177] Compared with Example 1, the 3d and 28d compressive strengths of Example 30 of the present application are reduced by 1.94 MPa and 2.49 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 1.03 MPa and 1.73 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Example 31 of the present application are reduced by 1.6 MPa and 2.04 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 0.81 MPa and 1.56 MPa, respectively, indicating that the hydroxypropyl methylcellulose ether provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0178] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 1 of the present application are reduced by 15.14 MPa and 24.92 MPa respectively, and the 3d and 28d flexural strengths are reduced by 2.99 MPa and 4.5 MPa respectively, indicating that the active activator provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0179] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 2 of the present application are reduced by 9.39 MPa and 12.44 MPa respectively, and the 3d and 28d flexural strengths are reduced by 2.35 MPa and 3.85 MPa respectively, indicating that the reinforcing agent provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

[0180] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 3 of the present application are reduced by 7.01 MPa and 10.64 MPa respectively, and the 3d and 28d flexural strengths are reduced by 2.11 MPa and 3.64 MPa respectively, indicating that the thickener provided in the present application has a good and stable effect on improving the strength of the repair mortar.

[0181] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 4 of the present application are reduced by 7.16MPa and 10.92MPa respectively, and the 3d and 28d flexural strengths are reduced by 2.17MPa and 3.67MPa respectively, indicating that the modified polymer dispersant provided in the present application has a good and stable effect on improving the strength of the repair mortar.

[0182] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 5 of the present application are reduced by 2.61 MPa and 4.08 MPa respectively, and the 3d and 28d flexural strengths are reduced by 0.85 MPa and 1.65 MPa respectively. Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 6 of the present application are reduced by 2.87 MPa and 4.4 MPa respectively, and the 3d and 28d flexural strengths are reduced by 0.96 MPa and 1.74 MPa respectively, indicating that the proportion range of the active activator provided in the present application has a good and stable effect on improving the strength of the quick-repair cement mortar.

[0183] Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 7 of the present application are reduced by 6.9 MPa and 11.03 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 2.03 MPa and 3.55 MPa, respectively. Compared with Example 1, the 3d and 28d compressive strengths of Comparative Example 8 of the present application are reduced by 8.74 MPa and 14.63 MPa, respectively, and the 3d and 28d flexural strengths are reduced by 2.3 MPa and 3.74 MPa, respectively. This shows that the compound use of silicate cement and phosphate cement provided in the present application has a good and stable effect on improving the strength of quick-repair cement mortar.

Claims

1. A quick-repair cement mortar, characterized in that: The invention comprises the following components in parts by weight: 30-35 parts of magnesium phosphate cement, 15-20 parts of silicate cement, 37.5-42.5 parts of fly ash, 32.5-37.5 parts of steel slag powder, 90-100 parts of quartz sand, 1-1.5 parts of active activator, 0.25-0.75 parts of reinforcing agent, 0.25-0.3 parts of thickener, 0.25-0.4 parts of water reducing agent and 66-77 parts of water; the active activator comprises water glass, sodium sulfate, sodium hydroxide and modified polymer dispersed in a weight ratio of (8-10): (5-7): (5-7): (15-20). The modified polymer dispersant is prepared by the following method: sodium styrene sulfonate, N,N-dimethylacrylamide, a chain initiator and a chain transfer agent in a molar ratio of (16-22): (3-6): (0.1-0.2): (0.1-0.2) are dissolved in a solvent, and then the temperature is raised to 75-85°C while stirring under the protection of an inert gas, reacting for 4-5 hours, and then distilling under reduced pressure for 1.5-2 hours to obtain a modified polymer dispersant; the reinforcing agent includes nanoparticles, triethanolamine and ethylenediaminetetraacetic acid in a weight ratio of (3-5): (2-4): (1-3).

2. The quick-repair cement mortar according to claim 1, characterized in that: The nanoparticles include nano silicon dioxide and nano titanium nitride in a weight ratio of (5-7): (3-6).

3. The quick-repair cement mortar according to claim 1, characterized in that: The particle size of the fly ash is 10-20 μm, and the particle size of the steel slag powder is 15-25 μm.

4. The quick-repair cement mortar according to claim 1, characterized in that: The quartz sand includes 20-40 mesh quartz sand, 40-80 mesh quartz sand and 80-120 mesh quartz sand in a weight ratio of (1-3): (3-7): (6-10).

5. The quick-repair cement mortar according to claim 1, characterized in that: The thickener is hydroxypropyl methylcellulose ether.

6. A method for preparing the quick-repair cement mortar according to any one of claims 1 to 5, characterized in that: The following steps are involved: The magnesium phosphate cement, silicate cement, fly ash, steel slag powder, quartz sand, active activator, reinforcing agent, thickener, water reducing agent and water are uniformly mixed according to weight to prepare the quick repair cement mortar.

Citation Information

Patent Citations

  • Concrete healant

    CN102898107A

  • Magnesium phosphate cement with good hydrolytic resistance and using method thereof

    CN105800979A